Smart contract in blockchain: an exploration of legal framework in Malaysia - Mohd. Zain, Nor Razinah; Engku Ali, Engku Rabiah Adawiah; Adeyemi, Adewale Abideen; Abdul Rahman, Hamizah (IIUM Press, International Islamic University Malaysia, 2019)
In 2017, the global Blockchain technology market was predicted to reach 339.5 million U.S. dollars in size and is forecasted to grow to 2.3 billion U.S. dollars by 2021. The smart contract has an increasing role in governing the legal relationship between the interested parties. This research explores the current position of smart contracts in Malaysia and the viability of the Malaysian framework in handling the latest development. This research adopts the qualitative and doctrinal legal approaches in analysing the current legal practice, the relevant statutes and the viability of the Malaysian legal framework. These approaches are necessary to be carried out in ensuring the workability of smart contracts in Blockchain. Additionally, the practices of smart contracts from international experiences are collected as case studies in this research. As a part of the findings, the researchers found that smart contracts are more or less similar to traditional contracts. Therefore, the requirements as stipulated under the Contract Act 1950 that are applicable in Malaysia must be followed accordingly. In this study, based on the nature of Blockchain technology, the researchers evaluate the current position of Malaysian laws in dealing with smart contracts. Additionally, the researchers also looked at the acceptable legal practice of smart contracts in Malaysia.